Sustainable logistics - Macharis, Cathy (Emerald, 2014)
This book will bring a state of the art overview of the research done in sustainable logistics. It will be structured along the four A's of sustainable logistics: 1 Awareness: it is important that companies and policy makers are aware of the effects of their activities and policies. New methods to estimate the effects of the logistic activities and the change towards more sustainable ways will be covered. 2 Avoidance: transport can be avoided by a better collaboration between actors (vertically and horizontally). Papers covering this topic will be introduced here. 3 Acting and shifting the goods to more environmental friendly modes or to the non peak hours. 4 Anticipation of new technologies: the use of more environmental friendly vehicles (electric,.LNG) within the logistic chain.
Includes index.
Keywords: Transportation -- General.; Sustainability.; Transport planning & policy.; Business logistics -- Environmental aspects.; elektronické knihy; electronic books